Smokeless Tobacco Warnings in Indian Mass Media: Intention and Attempts to Quit - Madewell, Zachary J.; Kolaja, Claire A. (Indian Journal of Medical and Paediatric Oncology, 2019)
Introduction: In India, over 200 million people use smokeless tobacco (SLT), which increases the risk of cancers. Studies have demonstrated mass media campaigns effectively reduce smoking tobacco prevalence, but few have assessed their impact on SLT cessation. Objectives: This study used data from the Global Adult Tobacco Surveys (GATS) in 2009–2010 and 2016–2017 to examine associations between SLT health warnings in mass media, and intention and attempts to quit using SLT. We also compared the proportion of SLT users who noticed mass media warnings between 2009–2010 and 2016–2017. Materials and Methods: Over 16,000 and 15,000 current SLT users from the GATS-1 and GATS-2, respectively, were used for analysis. Weighted logistic regression models were used to analyze associations between noticed health warnings on SLT packages, newspapers/magazines, television, radio, billboards, cinemas, internet, vehicles, and walls, and intention and attempts to quit SLT. Results: In final models, the odds of intention and attempts to quit were highest among those who noticed warnings in newspapers/magazines (adjusted odds ratio [AOR]: 1.50; 95% confidence interval [CI]: 1.30–1.74) and the internet (AOR: 1.60; 95% CI: 1.12–2.29), respectively. Warnings on SLT packages, television, billboards, radio, vehicles, and walls were also associated with increased cessation behavior. More noticed warnings on SLT packages, television, billboards, and newspapers/magazines in GATS-2 than GATS-1, but fewer heard radio warnings. Conclusions: Among Indian SLT users, we found evidence that SLT warnings in mass media may promote cessation behavior. Health warnings in mass media could play an important role in the overall strategy to reduce the morbidity and mortality associated with SLT use.
Keywords: Attempts to quit; cessation behavior; Indian adults; intention to quit; mass media; smokeless tobacco